2008
DOI: 10.1007/s10669-007-9154-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of particulate matter (PM10) in Warri metropolis, Nigeria

Abstract: This study examined the spatial distribution of particulate air pollution in the Warri metropolis. This was done to ascertain the differences between the distribution of particulate matter (PM10) in the urban area and the surrounding rural areas. To achieve this, the study generated data from field measurement of PM10 levels for the year 2003. Analysis of variance, the U-test, and simple regression statistical techniques were used to analyze the data. The major finding of the study was that the Warri metropoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…Several studies have also shown that the ambient levels of indoor and outdoor pollutants in many developing urban cities is substantial56789 and associated with huge cost in economic terms and mortality 5. There are various sources of environmental pollution including traffic-related air pollution (TRAP).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also shown that the ambient levels of indoor and outdoor pollutants in many developing urban cities is substantial56789 and associated with huge cost in economic terms and mortality 5. There are various sources of environmental pollution including traffic-related air pollution (TRAP).…”
Section: Introductionmentioning
confidence: 99%
“…Instrument background and pump flow was also examined prior to conducting each measurement session. The portable PM10 instrument were validated using the WHO air filter sampling technique, described in Efe and Efe (2008).…”
Section: Ground Particulate Measurementsmentioning
confidence: 99%
“…Sites in low-income [22], medium-income [23] and high-income [24] countries around the world were studied to generate data useful for the assessment of human exposure to PM. Even remote sites were investigated for a background comparison [25].…”
Section: Introductionmentioning
confidence: 99%